2007
DOI: 10.1038/sj.eye.6702775
|View full text |Cite
|
Sign up to set email alerts
|

Capturing myopia and hypermetropia ‘phenotypes’ without formal refraction

Abstract: Purpose Understanding genetic and environmental factors that together contribute to the development of myopia is an international research priority. We have investigated the feasibility and accuracy of identifying and classifying refractive error, without formal refraction, as a means of easily identifying affected individuals in a large-scale, non-ophthalmological, and population-based survey. Methods At age 44/45 years, members of the 1958 British birth cohort underwent a biomedical, community survey. Refrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Given that there are many studies that have used noncycloplegic techniques for studies on both children and adults, including large studies such as the Avon Longitudinal Study of Parents and Children (Williams et al. 1996) and the British Birth Cohort studies (Cumberland et al. 2007, 2008), an important question is whether noncycloplegic refractions can be adjusted to give an accurate cycloplegic refraction.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there are many studies that have used noncycloplegic techniques for studies on both children and adults, including large studies such as the Avon Longitudinal Study of Parents and Children (Williams et al. 1996) and the British Birth Cohort studies (Cumberland et al. 2007, 2008), an important question is whether noncycloplegic refractions can be adjusted to give an accurate cycloplegic refraction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous population‐based studies have determined familial refractive error status using objective or subjective refraction, in‐person interview and questionnaire responses . While subjective refraction is considered the gold standard it is time‐consuming and expensive . Questionnaire administration can decrease both the cost and the time taken to collect data .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] While subjective refraction is considered the gold standard 1 it is time-consuming and expensive. 9 Questionnaire administration can decrease both the cost and the time taken to collect data. 1 However, use of this method without validation may result in erroneous conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…37 Examining prescribed distance glasses like GUSTO showed a good sensitivity (80%) and specificity (89%). 38 The Singapore Malay Eye Study (populationbased, cross-sectional study), examined 2912 adults aged 40 to 80 years, and found that people with uncorrected myopia who do not wear spectacles was 4.5%. 39 We project that the rates of self-reported myopia in our study may be underestimated by approximately 4% and thus the true myopia rates are slightly higher.…”
Section: Discussionmentioning
confidence: 99%